Night-time sap flow is parabolically linked to midday water potential for field-grown almond trees - Fuentes, Sigfredo (2013)
To quantify night-time (S n) and diurnal (S d) tree water uptake, two sets of sap flow sensors (heat-pulse compensated) were installed per tree in the north-east and south-west sides of the trunk in three trees per treatment. There were two treatments: (1) control, irrigated with 100 % ETc (T100), and (2) deficit, irrigated at 60 % ETc (T60) with daily irrigations at the peak atmospheric demand (December–January). Normalised S n by trees was in the range of 15–25 % throughout the season, compared to normalised S d, for T100 and T60, respectively. Furthermore, S n was parabolically correlated to plant water status from the previous day, measured as midday stem water potential. We also found strong correlations between S n and nocturnal vapour pressure deficit for T100 and T60, indicating that nocturnal transpiration was significant for both treatments. Differences in S n were observed for the NE and SW sensors for T60, being significantly less for the NE side (sunny side) compared to the SW side (more shaded). No differences were observed for T100 regarding probe positioning.